Phenotype and toxicity of the recently discovered exlA‐positive Pseudomonas aeruginosa strains collected worldwide. (21st April 2016) - Reboud, Emeline; Elsen, Sylvie; Bouillot, Stéphanie; Golovkine, Guillaume; Basso, Pauline; Jeannot, Katy; Attrée, Ina; Huber, Philippe
Summary: We recently identified a hypervirulent strain of Pseudomonas aeruginosa, differing significantly from the classical strains in that it lacks the type 3 secretion system (T3SS), a major determinant of P. aeruginosa virulence. This new strain secretes a novel toxin, called ExlA, which induces plasma membrane rupture in host cells. For this study, we collected 18 other exlA ‐positive T3SS‐negative strains, analyzed their main virulence factors and tested their toxicity in various models. Phylogenetic analysis revealed two groups. The strains were isolated on five continents from patients with various pathologies or in the environment. Their proteolytic activity and their motion abilities were highly different, as well as their capacity to infect epithelial, endothelial, fibroblastic and immune cells, which correlated directly with ExlA secretion levels. In contrast, their toxicity towards human erythrocytes was limited. Some strains were hypervirulent in a mouse pneumonia model and others on chicory leaves. We conclude that (i) exlA ‐positive strains can colonize different habitats and may induce various infection types, (ii) the strains secreting significant amounts of ExlA are cytotoxic for most cell types but are poorly hemolytic, (iii) toxicity in planta does not correlate with ExlA secretion.